Correlation of AE and Fracture Intensity during Impact Indentation of Coal Block - S. J. Jung; A. W. Khair (The National Institute for Occupational Safety and Health (NIOSH), 1989)
"IntroductionIn a typical incremental loading test, the AE activity increases rapidly in the initial stage of the loading. It is associated with initial closure under compression of favorably oriented cracks already present, together with sliding of crack faces against each other /1/. After the initial stage, crack closure and movement largely cease and the AE activity drops to a barely detectable level /2/. In the final stage of loading test, cracking associated with the onset of inelastic deformation' occurs, and the rate of AE rapidly increases /3/ indicating an increase in the •number of events associated with higher number of microcracks. To understand better primary fragmentation process, Anderson and Ruzzi conducted tests to identify a practical method of monitoring fracture development in rock, as caused by an excavation tool /4/. They proved that a relationship existed between the AE activity, generated during fracturing and the amount of fracture surface area created.A process of fragmentation, demonstrated by conical bits acting orthogonal to the flat surface of block of coal specimen with and without lateral confining pressure is presented here. The monitoring of AE during the fracturing process of rock/coal has been a very useful indirect method in studying fracture mechanism.Specimen PreparationLarge blocks of Waynesburg coal were obtained from a surface mine. These blocks were then out and molded to approximate dimensions of 25.4 x 25.4 x 15.2 'an (10 x 10 x 6 in.). These specimens were instrumented with three strain gages in a 45 degree rosette. One was mounted parallel to the bedding plane direction, another was tinted at an angle of 45 degree from the bedding plane direction and the third was mounted perpendicular to the bedding .plane direction. Each of the three strain gages were set 5.1 an (2 in.) away from the impact point.Typical Test ProcedureIn a typical experiment, the specimen was placed in the confining chamber.Predetermined equivalent in-situ stresses were applied to the specimen by using two sets of hydraulic cylinders. Two 1 in. thick steel plates ware positioned between the sample and the hydraulic cylinders in order to distribute the pressure uniformly over the whole surface of the specimen. The LVDT null position was adjusted with respect to the coal face. After setting the LVDT, the bit and associated weight was lifted to a predetermined height (equivalent to a predetermined kinetic energy) by a win. The three strain gages were balanced using the signal conditioner and the output was recorded by a 6 channel strip chart recorder. The experimental set-up is shown in Figure 1."